Rapid Development of High-Level Resistance to Dolutegravir With Emergence of T97A Mutation in 2 Treatment-Experienced Individuals With Baseline Partial Sensitivity to Dolutegravir. (8th September 2018) - George, Jomy M; Kuriakose, Safia S; Dee, Nicola; Stoll, Pam; Lalani, Tahaniyat; Dewar, Robin; Khan, Muhammad A; Rehman, Muhammad T; Grossman, Zehava; Maldarelli, Frank; Pau, Alice K
Abstract: HIV integrase mutation T97A emerges after suboptimal therapy with integrase strand transfer inhibitors (INSTIs), but the contribution of T97A to dolutegravir resistance remains uncertain. Here we report >10-fold increase in dolutegravir resistance after the single addition of T97A in 2 individuals with prior INSTI resistance receiving dolutegravir salvage therapy.